(untitled) (Circe de clásicos y modernos, 2021)
This paper studies the fraught chapter (V.7) of the Nicomachean Ethics concerning natural justice. It argues that the main tradition of commentary on the chapter has strayed onto a wrong path by misconstruing two quite precise junctures in the argument. When those two errors are corrected, there emerges an Aristotle who, far from being a champion of natural law theory in ethics, holds that the moral principles with which humans are naturally endowed are variable, and that in two senses. Not only do these moral principles vary across space and time, but also they can be deliberately modified by habituation.